2014
DOI: 10.3390/atmos6010050
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and Horizontal Polarization Observations of Slowly Varying Solar Emissions from Operational Swiss Weather Radars

Abstract: Abstract:The electromagnetic power that arrives from the Sun in the C-band has been used to check the quality of the polarimetric, Doppler weather radar network that has recently been installed in Switzerland. The operational monitoring of this network is based on the analysis of Sun signals in the polar volume data produced during the MeteoSwiss scan program. It relies on a method that has been developed to: (1) determine electromagnetic antenna pointing; (2) monitor receiver stability; and (3) assess the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 8 publications
0
34
2
Order By: Relevance
“…In Section 4.1 of Gabella et al [5], it has been shown that the three series of precise 10.7 cm measurements acquired by DRAO are in practice undistinguishable in terms of comparison with radar observations. In this paper, similar to Gabella et al [5], the daily radar values presented in Section 3.3 will be evaluated against the 20 UTC dataset, which is used as the reference for quantitatively assessing the degree of agreement.…”
Section: Daily Measurements Of Solar Flux At S-bandmentioning
confidence: 99%
See 2 more Smart Citations
“…In Section 4.1 of Gabella et al [5], it has been shown that the three series of precise 10.7 cm measurements acquired by DRAO are in practice undistinguishable in terms of comparison with radar observations. In this paper, similar to Gabella et al [5], the daily radar values presented in Section 3.3 will be evaluated against the 20 UTC dataset, which is used as the reference for quantitatively assessing the degree of agreement.…”
Section: Daily Measurements Of Solar Flux At S-bandmentioning
confidence: 99%
“…In this paper, similar to Gabella et al [5], the daily radar values presented in Section 3.3 will be evaluated against the 20 UTC dataset, which is used as the reference for quantitatively assessing the degree of agreement.…”
Section: Daily Measurements Of Solar Flux At S-bandmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration of radar systems using the Sun as a radio source was first proposed by Whiton et al (1976) and developed in several works by Tapping (2001a), Holleman and Beekhuis (2004), Huuskonen and Holleman (2007), Holleman et al (2010a), Huuskonen et al (2014), Gabella et al (2014) and Altube et al (2015). The Sun is used for monitoring the receiver calibration, the alignment of the radar antenna and checking the antenna gain (Rinehart, 2004).…”
Section: Sun Calibrationmentioning
confidence: 99%
“…Over the years, many calibration techniques based on external sources have been developed, e.g., calibration with the Sun, and ones based on fixed and well-known targets, e.g., calibration with ground clutter echoes. The calibration using the solar interferences was first proposed by Whiton et al (1976) and has been subsequently applied on operational radars for the monitoring of the radar receiver chain and antenna pointing (Holleman and Beekhuis, 2004;Huuskonen and Holleman, 2007;Holleman et al, 2010a, b;Huuskonen et al, 2014;Gabella et al, 2014 andAltube et al, 2015). The ground clutter calibration allows the stability of the radar calibration to be monitored automatically, specifically the transmitting and receiving chain of both polarization channels, through statistical analysis of the echo power return from fixed targets (Silberstein et al, 2008 andWolff et al, 2015).…”
Section: Introductionmentioning
confidence: 99%